Towards a revision of the bamboo corals (Octocorallia): Part 5, new genera and species of Keratoisididae from the Tasmanian deep sea - Lapointe, Abby; Watling, Les (Zootaxa, 2022)
Four new genera and six new species of deep-sea bamboo corals (Family: Keratoisididae) from the seamounts off the eastern and southern coast of Tasmania are described and illustrated. In situ high-definition images from remotely operated vehicles, compound microscopy, and Scanning Electron Microscopy (SEM) of 29 specimens collected at depths of 729 to 3950 m were used to provide data on distinguishing morphological characters. The species described include two new species in the genus Keratoisis, two species in the newly described genus Adinisis, and one species each in the new genera Tanyostea and Dokidisis. The species Keratoisis magnifica and Lepidisis solitaria are re-assigned to the newly described genus Onkoisis due to the shape and design of the polyp arrangement and sclerites, which differ considerably from that of the type species of Keratoisis.